Comparative study of LMI-based output feedback spr synthesis for plants with different numbers of inputs and outputs - Covacic, Márcio R.; Teixeira, Marcelo C.M. [UNESP]; Assunção, Edvaldo [UNESP]; Cardim, Rodrigo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
New Linear Matrix Inequalities (LMI) conditions are proposed for the following problem, called Strictly Positive Real (SPR) synthesis: given a linear time-invariant plant, find a constant output feedback matrix Ko and a constant output tandem matrix F for the controlled system to be SPR. It is assumed that the plant has the number of outputs greater than the number of inputs. Some sufficient conditions for the solution of the problem are presented and compared. These results can be directly applied in the LMI-based design of Variable Structure Control (VSC) of uncertain plants. ©2008 IEEE.
Keywords: Control theory; Feedback; Linear control systems; Matrix algebra; Spectrum analyzers; Comparative studies; Linear time invariants; Output feedbacks; Strictly positive real; Variable structure systems; Linear matrix inequalities